2019
DOI: 10.3389/fpls.2019.00663
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Thermospermine Synthase Activity in Vascular and Non-vascular Plants

Abstract: In plants, the only confirmed function for thermospermine is regulating xylem cells maturation. However, genes putatively encoding thermospermine synthases have been identified in the genomes of both vascular and non-vascular plants. Here, we verify the activity of the thermospermine synthase genes and the presence of thermospermine in vascular and non-vascular land plants as well as in the aquatic plant Chlamydomonas reinhardtii . In addition, we provide information about differential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…T-Spm has been identified as a plant growth regulator that represses xylem differentiation and promotes stem elongation by preventing premature death of developing xylem vessel elements in Arabidopsis (Kakehi et al, 2008;Muñiz et al, 2008;Vera-Sirera et al, 2010). However, ACL5 expression and the presence of T-Spm were recently found in non-vascular land plants and in the unicellular green alga Chlamydomonas reinhardtii (Solé-Gil et al, 2019), which suggested that T-Spm plays also other roles in addition to xylem development in vascular plants. Our present results show a novel function for ACL5 in the morphologically necrotic cell death and support the view of the genetic regulation of necrosis in Scots pine embryogenesis and further in plant development.…”
Section: Discussionmentioning
confidence: 99%
“…T-Spm has been identified as a plant growth regulator that represses xylem differentiation and promotes stem elongation by preventing premature death of developing xylem vessel elements in Arabidopsis (Kakehi et al, 2008;Muñiz et al, 2008;Vera-Sirera et al, 2010). However, ACL5 expression and the presence of T-Spm were recently found in non-vascular land plants and in the unicellular green alga Chlamydomonas reinhardtii (Solé-Gil et al, 2019), which suggested that T-Spm plays also other roles in addition to xylem development in vascular plants. Our present results show a novel function for ACL5 in the morphologically necrotic cell death and support the view of the genetic regulation of necrosis in Scots pine embryogenesis and further in plant development.…”
Section: Discussionmentioning
confidence: 99%
“…SAMDC activity, has been detected in different compartments after subcellular fractionation in different plant species (Bagni & Tassoni, 2001; Kumar, Taylor, Altabella, & Tiburcio, 1997), but in silico analysis of A. thaliana SAMDC sequences suggests nuclear and cytosolic locations for this enzyme (B. Belda‐Palazón, personal communication), a view supported by experimental evidences obtained with other plant species (Liu et al, 2014). In addition to the ‘usual’ PAs, a wide range of vascular and non‐vascular plants also synthesise thermospermine (tSpm) (Solé‐Gil, Hernández‐García, López‐Gresa, Blázquez, & Agustí, 2019), a structural isomer of Spm produced by the thermospermine synthase ACL5 (EC 2.5.1.79). This tetraamine is involved in xylem differentiation (Muñiz et al, 2008), but might also have other roles (Solé‐Gil et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ‘usual’ PAs, a wide range of vascular and non‐vascular plants also synthesise thermospermine (tSpm) (Solé‐Gil, Hernández‐García, López‐Gresa, Blázquez, & Agustí, 2019), a structural isomer of Spm produced by the thermospermine synthase ACL5 (EC 2.5.1.79). This tetraamine is involved in xylem differentiation (Muñiz et al, 2008), but might also have other roles (Solé‐Gil et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic studies have suggested that the SPDS genes of the various organisms derive from a common ancestor preceding the separation between prokaryotes and eukaryotes and that they have been the origin of SPMS and TSPMS activities through gene duplication and/or neofunctionalization 16 . Moreover, it has been hypothesized that plants acquired TSPMS early during evolution by horizontal gene transfer from archaea or bacteria 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have been performed on the evolutionary pathways of genes involved in polyamine biosynthesis 10 , 11 , 16 18 , 48 , comparatively less is known about the evolutionary history of genes involved in polyamine catabolism. Most studies have focused on the genomic identification and biochemical characterization of PAO isoforms from single species and therefore they used phylogenetic methods mainly for delimiting clusters and subfamilies to which to assign PAO isoforms 49 51 .…”
Section: Introductionmentioning
confidence: 99%